Development of Educational Game for Primary School Mathematics using Microsoft Kinect - Teddy Surya Gunawan; Bakhtiar Bahari; Mira Kartiwi (Institute of Advanced Engineering and Science, 2017)
This research focuses on the design and development educational game using Microsoft Kinect. The edugame can be used as educational tool in a classroom as to create an interesting and interactive learning process. This research is also focused on mathematics as its educational content using Microsoft Visual C#, XNA Game Studio, Microsoft Kinect for Windows SDK, and Microsoft Kinect as the main hardware. There are about eleven topics regarding mathematics based on the module provided by the Malaysian Ministry of Education. The interface of the game has been designed and developed to be interactive and attractive using some cartoon graphics, such as Ipin, Boboiboy, and Yaya. The developed game is a quiz base program, where student will have 10 questions each round and 4 choices of answers for every question. Currently, this educational game is designed for Year 1, Year 2 and Year 3 primary school students, and it has been evaluated by a group of 8 students. Furthemore, it has been evaluated and validated by a school teacher, in which they confirm the effectiveness of the developed game to improve student’s learning on Mathematics.